Gender, financial risk, and probability weights - Helga Fehr-Duda; Manuele de Gennaro; Renate Schubert (ETH Zurich, CER-ETH - Center of Economic Research, 2004)
Women are commonly stereotyped as more risk averse than men in financial decision making. In this paper we examine whether this stereotype reflects actual differences in risk taking behavior by means of a laboratory experiment with monetary incentives. Gender differences in risk taking may be due to differences in subjects' valuations of outcomes or to the way probabilities are processed. The results of our experiment indicate that men and women differ in their probability weighting schemes; however, we do not find a significant difference in the value functions. Women tend to be less sensitive to probability changes and also tend to underestimate large probabilities of gains to a higher degree than do men, i.e. women are more pessimistic in the gain domain. The combination of both effects results in significant gender differences in average probability weights in lotteries framed as investment decisions. Women's relative insensitivity to probabilities combined with pessimism may indeed lead to higher risk aversion.
Keywords: D81; C91; C92; 330; Gender Differences; Risk Aversion; Financial Decision Making; Prospect Theory; Risikoaversion; Geschlecht; Theorie